Phenological segregation suggests speciation by time in the planktonic diatom Pseudo‐nitzschia allochrona sp. nov. Issue 8 (4th August 2022) - Percopo, Isabella; Ruggiero, Maria Valeria; Sarno, Diana; Longobardi, Lorenzo; Rossi, Rachele; Piredda, Roberta; Zingone, Adriana
Abstract: The processes leading to the emergence of new species are poorly understood in marine plankton, where weak physical barriers and homogeneous environmental conditions limit spatial and ecological segregation. Here, we combine molecular and ecological information from a long‐term time series and propose Pseudo‐nitzschia allochrona, a new cryptic planktonic diatom, as a possible case of speciation by temporal segregation. The new species differs in several genetic markers (18S, 28S and ITS rDNA fragments and rbc L) from its closest relatives, which are morphologically very similar or identical, and is reproductively isolated from its sibling species P. arenysensis . Data from a long‐term plankton time series show P. allochrona invariably occurring in summer–autumn in the Gulf of Naples, where its closely related species P. arenysensis, P. delicatissima, and P. dolorosa are instead found in winter–spring. Temperature and nutrients are the main factors associated with the occurrence of P. allochrona, which could have evolved in sympatry by switching its phenology and occupying a new ecological niche. This case of possible speciation by time shows the relevance of combining ecological time series with molecular information to shed light on the eco‐evolutionary dynamics of marine microorganisms. Abstract : We describe a new cryptic species in the marine diatom genus Pseudo‐nitzschia, P. allochrona, based on different phylogenetic markers and with the support of mating incompatibility with the sibling species P. arenysensis . Compared with its closest congeneric species in the Gulf of Naples, P. allochrona occupies a distinct temporal niche, which suggests it may have evolved in sympatry by switching its phenology and occupying a new ecological niche.